Building a safer workplace: factors influencing healthy work place among teaching staff in selected universities (2017)
The study, examined the combined influences of workplace environmental factors; work load, role ambiguity/conflict and class size on the work stress and wellbeing among academic staff in federal universities in the South-west, Nigeria. This study adopted the descriptive research design survey type. Four of the oldest federal universities in the South-west were purposively selected. The choice of these universities was based on the fact that, they belong to the group of the oldest federal-owned universities, with large number of lecturers and similar conditions of Service, large proportion of staff as well as substantial volume of task. The universities were stratified into existing faculties; seven faculties were selected from three of the universities (Universities of Ibadan, University of Lagos, Obafemi Awolowo University and Federal University of Agriculture, Abeokuta). The multistage sampling technique was used to select 1000 academic staff across the tour universities. Standardised instrument was used for data collection. Data were analysed using descriptive statistics of Pearson product moment correlation and multiple regressions at 0.05 level of significance. Results demonstrated that workplace environmental factors; work load, role ambiguity/conflict and class size accounted for 2% of change observed in (F(3,997)=12.07; R=0.19, p<.001). Work load (r=0.09) was the most important predictor of work stress and wellbeing; while class size, role ambiguity/conflict, protection, friendship and collegiality did not. Advice (r=-. 18, p<.05), feedback appraisal (r= 10, p<.05) and connectedness (r= -. 18, p<.05) predicted stress levels among academic staff. Institutional support variables; research assistance (r= -. 10, p<.05), opportunity(r= 17, p<.05) and promotion (r= 14, p<.05) were associated with lower stress levels. It was concluded that unavailability of flexible work load positively determined the work stress and wellbeing among academic staff in federal universities in the South-west Nigeria. The study submits that there is the need to improve upon the social support while effective institutional support should be provided toreduce work stress and improve the wellbeing among academic staff in the universities.